Association between Daily Hydrogen Sulfide Exposure and Incidence of Emergency Hospital Visits: A Population-Based Study - Finnbjornsdottir, Ragnhildur Gudrun (PLoS One, 2016)
BACKGROUND: The adverse health effects of high concentrations of hydrogen sulfide (H(2)S) exposure are well known, though the possible effects of low concentrations have not been thoroughly studied. The aim was to study short-term associations between modelled ambient low-level concentrations of intermittent hydrogen sulfide (H(2)S) and emergency hospital visits with heart diseases (HD), respiratory diseases, and stroke as primary diagnosis. METHODS: The study is population-based, using data from patient-, and population-registers from the only acute care institution in the Reykjavik capital area, between 1 January, 2007 and 30 June, 2014. The study population was individuals (≥18yr) living in the Reykjavik capital area. The H(2)S emission originates from a geothermal power plant in the vicinity. A model was used to estimate H(2)S exposure in different sections of the area. A generalized linear model assuming Poisson distribution was used to investigate the association between emergency hospital visits and H(2)S exposure. Distributed lag models were adjusted for seasonality, gender, age, traffic zones, and other relevant factors. Lag days from 0 to 4 were considered. RESULTS: The total number of emergency hospital visits was 32961 with a mean age of 70 years. In fully adjusted un-stratified models, H(2)S concentrations exceeding 7.00μg/m(3) were associated with increases in emergency hospital visits with HD as primary diagnosis at lag 0 risk ratio (RR): 1.067; 95% confidence interval (CI): 1.024–1.111, lag 2 RR: 1.049; 95%CI: 1.005–1.095, and lag 4 RR: 1.046; 95%CI: 1.004–1.089. Among males an association was found between H(2)S concentrations exceeding 7.00μg/m(3), and HD at lag 0 RR: 1.087; 95%CI: 1.032–1.146 and lag 4 RR: 1080; 95%CI: 1.025–1.138; and among those 73 years and older at lag 0 RR: 1.075; 95%CI: 1.014–1.140 and lag 3 RR: 1.072; 95%CI: 1.009–1.139. No associations were found with other diseases. CONCLUSIONS: The study showed an association between emergency hospital visits with HD as primary diagnosis and same day H(2)S concentrations exceeding 7.00μg/m(3), more pronounced among males and those 73 years and older than among females and younger individuals.